TEACHING SPEAKING TO A2 LEVEL LEARNERS THROUGH MIND MAPPING - Bekbergenova Gulayim Ayjarikovna; Tolibaeva Kamila Timurovna (TADQIQOTLAR, 2026)
Abstract: Teaching speaking to A2 level learners is a rewarding yet challenging task for educators. At this proficiency level, learners are developing their ability to communicate basic ideas, express opinions, and interact in simple conversations. However, they may still lack confidence, have limited vocabulary, and encounter difficulties with fluency and organizing their thoughts. Mind mapping can serve as an effective tool to address these challenges and enhance the speaking skills of A2 level learners. This article will explore the benefits of mind mapping in the language classroom, provide practical strategies for implementation, and discuss the positive outcomes it brings to both students and teachers.